2019
DOI: 10.21037/atm.2019.01.68
|View full text |Cite
|
Sign up to set email alerts
|

Association between carotid plaque and Parkinson’s disease

Abstract: Background: Epidemiological studies show that patients with Parkinson's disease (PD) are prone to have a reduced incidence of ischemic cerebrovascular disease. Previous studies show the correlation between PD and the lipids serum levels. The PD,s patients are found with a reduced serum level of triglyceride and low-density lipoprotein cholesterol (LDL-C); thus, the level of serum uric acid (UA) is closely related to the occurrence and development of PD. Patients with low serum UA levels have a higher chance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
3
4
0
Order By: Relevance
“…Conversely, Marsala et al [33] reported a lower CIMT in 30 PD patients with a mean disease duration of 13 years, when compared to a matched control group with the same demographic characteristics. Finally, in parallel to our negative results, Yan et al [36] and Lee et al [28] did not find differences between early stages of PD and controls regarding CIMT. As suggested in a previous study, Yan et al [36] also reported that disease duration was correlated with CIMT, which we could not evaluate since we only included early‐stage PD patients.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Conversely, Marsala et al [33] reported a lower CIMT in 30 PD patients with a mean disease duration of 13 years, when compared to a matched control group with the same demographic characteristics. Finally, in parallel to our negative results, Yan et al [36] and Lee et al [28] did not find differences between early stages of PD and controls regarding CIMT. As suggested in a previous study, Yan et al [36] also reported that disease duration was correlated with CIMT, which we could not evaluate since we only included early‐stage PD patients.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, in parallel to our negative results, Yan et al [36] and Lee et al [28] did not find differences between early stages of PD and controls regarding CIMT. As suggested in a previous study, Yan et al [36] also reported that disease duration was correlated with CIMT, which we could not evaluate since we only included early‐stage PD patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Patients with PD commonly experience the symptoms and signs of tremor, bradykinesia, rigidity, and uncontrollable movements [ 89 , 90 , 91 ]. All of the pathological variables that contribute to the development of clinical complexity in PD include inappropriate protein aggregation, oxidative stress, neuroinflammation, mitochondrial damage, and genetic anomalies [ 92 , 93 ].…”
Section: The Relationship Between Parkinson’s Disease Heart Brain And...mentioning
confidence: 99%